PENGARUH KREATIVITAS IKLAN DAN ATRIBUT PRODUK TERHADAP MINAT BELI AC MEREK X DI JAKARTA BARAT - Bob Harhari (Universitas Mercu Buana, 2014)
Abstract: This study aims to determine the effect of advertising creativity and product attributes against AC Brand Xdi buying interest kotamadyaJakarta West. The study was descriptive. Data obtained by distributing questionnaires using cluster sampling methodwith a total sample of 100 respondents. Data were tested using the test of validity, reliability, and the classical assumption, and analyzed by multiple linear regression using the software SPSS17.Hasil show that in partial advertising creativity affect the buying interest but the variable product attributes do not affect the buying interest. Variables simultaneously advertising creativity and product attributes affect the buyinginterest. Variables advertising creativity gives greater influence on the buying interest, compared to the variable product attributes. The influence of the independent variables and product attributes advertising creativity for 66.0% of the dependent variable buying interest, while the remaining 34.0% influenced by other factors.Keywords: creative advertising, product attributes, buying interest, cluster sampling.